Penerapan Model Pembelajaran Kooperatif Tipe Times Games Tournament (TGT) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi - Wafa Ainur Rahima; Ati Sadiah; Ai Nursolihat (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the low student learning outcomes in Economics subjects caused by the learning process that is still centered on the teacher, which is not optimal. This study aims to determine the effect of the cooperative learning model of the Teams Games Tournament (TGT) type in improving student learning outcomes on the material of price index and inflation. The study used a quasi-experimental method with a Pretest-Posttest Nonequivalent Control Group Design. The research sample consisted of two classes, namely the experimental class and the control class, each of which consisted of 38 students. Data collection techniques used tests in the form of pre-test and post-test. Data analysis was carried out through normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and effect size tests. The results showed that the application of the Teams Games Tournament (TGT) learning model was able to improve student learning outcomes significantly. This was indicated by the average post-test score of the experimental class of 88.32, higher than the control class of 80.26, with a significance value of 0.000 <0.05. Furthermore, the effect size calculation of 1.08 indicates a significant impact of the TGT model on student learning outcomes. The TGT model also has a nurturing effect, developing students' collaborative skills during learning. Therefore, the Teams Games Tournament (TGT) learning model is effective in improving student learning outcomes in Economics.